Penyuluhan Imunisasi Tetanus Toksoid Untuk Calon Pengantin Dan Wanita Usia Subur Di Fasilitas Kesehatan Tingkat Pertama - Rina kusumaratna; Suriyani Tan; Witriastika Suci (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
Tetanus is a serious disease caused by spores of the bacterium Clostridium tetani. Tetanus infection has no boundaries as people of all ages can be infected and it is still a public health problem today, especially for pregnant women and newborns. Neonatal tetanus (TN) is the tetanus infection in infants aged 3 – 28 days after birth and maternal tetanus (MT) is the infection that occurs during pregnancy and up to 6 weeks after delivery. Tetanus infection generally occurs if the delivery is not carried out in health facilities with adequate equipment and is known as one of the most common causes of death during childbirth. The aim of this Community Service activity was to provide counseling about the importance of Tetanus Toxoid (TT) T immunization for prospective brides and WUS who came to the mother and children out-patient clinic at the Primary Health Care. Cadres those bearing an important role in expanding health information for the community were also involved in this program. This Community Service activity held counseling for the prospective bride and fertile-aged women, while the cadres were given refreshing additional knowledge about TT immunization. The results of this activity were increasing the cadres’ knowledge about TT immunization, and those prospective-bride and fertile-aged women were also encouraged to carry out active TT immunization at the Primary Health Care. There is also a need for cross-sector collaboration with the Religious Affairs office in the application of evidence of TT immunization for prospective-bride as a mandatory requirement that could be implemented properly.